Factors promoting and hinding the expression of teachers’ creativity - Gevorgyan, Astghik (Bulletin of Yerevan University E: Philosophy, Psychology, 2024)
In order to adapt the changes in the educational system to the imperatives of time, a creative and flexible approach and a transformation of the traditional education model is needed, which will provide an opportunity to ensure the formation of new skills for students. In this case, the role of the creative teacher as an example for the student is paramount. The purpose of the article is to present the factors contributing to and hindering the manifestation of teachers’ creativity, their peculiarities in the Armenian environment. For this purpose, the approaches to creativity in the field of education and the factors contributing to and hindering the manifestation of creativity were studied. Based on the approaches of creativity theorists such as Nelke, Lubart and Rogers, a questionnaire was prepared, which was used as a research method for the study of experts in the field of education and teachers. The analysis of the experimental data showed that experts expect teachers to show creativity that will comply with system constraints, based more on the initiative and motivation of the teacher than on rewards and external environmental conditions. Meanwhile, teachers emphasize not only the presence of their personal creative qualities, but also the recognition and reward of their work by the external environment.